RIPRAN – one of the best project risk analysis methodologies - Bockova Katerina; Daniel Lajcin (Managerial Economics)
Project risk management is an important aspect of project management. According to the PMBoK, risk management is one of the ten knowledge areas in which a project manager must be competent. Project risk management remains a relatively undeveloped discipline, distinct from the risk management used by operational, fi nancial, and underwriters’ risk management. This gulf is due to several factors: risk aversion (especially public understanding and risk in social activities), confusion in the application of risk management to projects, and the additional sophistication of probability mechanics above those of accounting, fi nance, and engineering.The aim of the presented paper is to demonstrate how to use RIPRAN (the Czech project for risk analysis) as a main part of a feasibility study of a new product project in a manufacturing company. To fulfi ll this primary aim, we formulated these secondary aims:– To provide a critical analysis of the available information sources dealing with risk management in new product projects in manufacturing companies.– To study and profoundly understand RIPRAN, project risk analysis, its history, application, principles, rules, and exceptions.– To discuss with the author of RIPRAN about the RIPRAN application in new product projects in manufacturing companies of non-Czech origin.– To compile a feasibility study of the new product project.All of these highly cited secondary aims were fulfi lled. A short overview of the risk management topic as well as RIPRAN’s characteristics and defi nition are part of the presented paper. To process this theoretical part of the paper, we used mostly analysis, synthesis, comparison, and deduction. We studied monographs, journals, and internet links with the impact of a source's topicality. The used sources are cited in the list of references. During the process of a feasibility study of a new product project provided through the analysis of our own experience, we discussed the application of the RIPRAN method to the new product project with the author of this method. We realized e-mail correspondence, phone discussions, and fi nally a personal meeting to control the whole RIPRAN analysis document and discuss the method’s application in the non-Czech origin business environment. To fulfi ll the primary aim of the presented paper, we decided to use the case study method.